Remote Control of T Cell Activation Using Magnetic Janus Particles. Issue 26 (4th May 2016) - Lee, Kwahun; Yi, Yi; Yu, Yan
Abstract: We report a strategy for using magnetic Janus microparticles to control the stimulation of T cell signaling with single‐cell precision. To achieve this, we designed Janus particles that are magnetically responsive on one hemisphere and stimulatory to T cells on the other side. By manipulating the rotation and locomotion of Janus particles under an external magnetic field, we could control the orientation of the particle–cell recognition and thereby the initiation of T cell activation. This study demonstrates a step towards employing anisotropic material properties of Janus particles to control single‐cell activities without the need of complex magnetic manipulation devices. Abstract : Janus particles were employed to control T cell activation. The particles were magnetically responsive on one side and displayed ligands for T cell stimulation on the other side. T cell activation was remotely controlled by simultaneously manipulating the rotation and locomotion of the magnetic Janus particles.